Model of Impulsive Buying Behavior in Shopee Live: Study of Demand, Convenience, Interactivity, and Playfulness Through Perceived Usefulness - Amalia Nursyamsiah; Mahir Pradana; Arry Widodo (JOURNAL OF MANAGEMENT, ACCOUNTING, GENERAL FINANCE AND INTERNATIONAL ECONOMIC ISSUES, 2025)
Indonesia has seen significant growth in the e-commerce sector, characterized by rapid growth rates. E-commerce gives businesses a new feature with the aim of stimulating consumers to buy products. The live shopping feature on e-commerce platforms is now seen as the latest trend that also serves as a new channel, method, and experience for consumers in doing shopping activities. This research uses the SOR theory derived from the field of environmental psychology which explains how environmental stimuli can influence a person's response and impact the person's behavior. The objective of this research is to examine how live streaming shopping activates impulsive purchases through cognitive processes involving perceived usefulness, as influenced by factors like demand, convenience, interactivity, and playfulness. Through data analysis, demand, convenience, interactivity, and playfulness have a positive and significant influence on impulsive buying through perceived usefulness. It is important to keep in mind that since this study only examined Shopee Live users in Indonesia, the findings may not apply in other countries or circumstances. To examine the influence of demand, convenience, interactivity, and playfulness on impulsive buying through perceived usefulness in various contexts, further research can be conducted in other countries or focusing on several regions in Indonesia. A deeper insight into consumer behavior in the realm of live streaming shopping can be achieved by exploring other elements that might impact impulsive purchases. This can be done by thoroughly analyzing the various factors at play.